Transformasi UMKM Desa Karanganyar Menuju Legalitas Usaha Melalui OSS - Muhammad Bahrul Ulum; Indah Nofita Sari; Eva Kurnia Setiawan (Yayasan Literasi Altruis Khatulistiwa, 2025)
Community service program this community service program aims to empower Micro, Small, and Medium Enterprises (MSMEs) actors in Karanganyar Village, Bantaran District, through the utilization of the Medium Enterprises (MSMEs) in Karanganyar Village, Bantaran Subdistrict, through the utilization of Online Single Submission (OSS) in the business legality process. Online Single Submission (OSS) in the business legality process. Business legality is important for MSME actors in order to access capital, obtain legal protection, and utilize government assistance programs. legal protection, and take advantage of government assistance programs. However, there are still many MSME actors who do not have a business license due to a lack of understanding of the importance of legality and limited access to OSS technology the importance of legality and limited access to OSS technology. This program includes several stages, starting from socialization on the importance of business legality, training on the use of OSS, to technical assistance in the process of the importance of business legality, training on the use of OSS, and technical assistance in the process of process of registering business legality. In addition, the program also provides free internet access at the village service center to support the online registration process. online registration process. Through this program, it is expected that MSME players in Karanganyar Village can increase their awareness of the importance of business legality, and be able to utilize OSS technology independently. Able to utilize OSS technology independently. The expected result of this program is an increase in the number of MSMEs that have business licenses, easier access to capital, and an increase in their business capacity. easier access to capital, and an increase in their business capacity. The success of this program will be evaluated through continuous monitoring of MSME actors, to ensure that they can manage their businesses effectively after obtaining legal effectively after obtaining legality